The versatility of the serratus anterior free flap in head and neck reconstruction. (9th June 2016) - Khan, Mohemmed N.; Rodriguez, Laureano Giraldez; Pool, Christopher D.; Laitman, Benjamin; Hernandez, Christopher; Erovic, Boban M.; Teng, Marita S.; Genden, Eric M.; Miles, Brett A.
Abstract : Objectives/Hypothesis: Review the literature on the use of the serratus anterior free flap in the head and neck reconstruction and describe new applications of the serratus anterior free flap. Study Design: Case series with retrospective chart review and literature review. Methods: A PubMed literature review was performed using the search terms "serratus free flap, " "serratus skull base, " "serratus scalp, " and "serratus free tissue transfer." One hundred and seventy‐six articles were identified, 22 of which included at least one head and neck reconstructive case utilizing the serratus free flap. Twenty‐two articles were identified since 1982 that discussed the use of the serratus anterior free flap for reconstruction in the head and neck. However, most of these were harvested in conjunction with latissimus muscle. Results: We present a case series of 15 patients in whom the serratus anterior muscle free flap was used alone for head and neck reconstruction. In seven of these patients, we used the serratus for coverage of the newly created pharynx after total laryngectomy, which has not previously been reported. Conclusion: The serratus anterior free muscle flap has great versatility in reconstruction of the head and neck. Because of its low donor site morbidity, thinness, and pliability, as well as its ease of harvest, it is ideal for reconstruction of the skull base and scalp. We have also found that it is ideal for muscle coverage of the newly reconstructed pharynx after total laryngectomy. Level of Evidence: 4. Laryngoscope, 127:568–573, 2017